IMPLEMENTASI KEBIJAKAN PELAYANAN ADMINISTRASI BERBASIS SISTEM APLIKASI E-OFFICE PADA UNIT LAYANAN ADMINISTRASI PEMERINTAH PROVINSI SULAWESI UTARA - Karen Betsy Linelejan (GoAcademica Research dan Publishing, 2021)
The purpose of this study is to find out how the implementation of administrative service policies based on the E-Office application system at the North Sulawesi Provincial Government Administration Service Unit, the factors that support and hinder the implementation of policies, as well as the efforts made to overcome obstacles. The research method used is descriptive research method with an inductive approach. The data collection techniques used in this study were in the form of observation, interviews, and documentation. The implementation of administrative service policies based on the E-Office application system at the Administrative Service Unit of the North Sulawesi Provincial Government is still not going well due to resource factors and bureaucratic structures that have not been running well. The problems that occur are that there are still employees who do not understand the existing E-Office system, the level of education of employees whose majority is high school and there are still junior high school education levels, problems related to Standard Operating Procedures, where there are still delays in handling files. , as well as related to the service of incoming mail for bureaus which cannot be implemented because of the problematic E-Office application system.